AN EXPLORATORY SURVEY ON THE TOPIC INTEGRATED MANAGEMENT SYSTEMS - Trierweiller, Andréa Cristina (2016)
The aim of this article is to analyse publications about Integrated Management Systems (IMS) and identify research opportunities. We conducted a literature review using the software EndNote to index the articles, and identified features related to IMS based on a systemic analysis. The interest of firms in implementing standards for Quality, Environmental, and Occupational Health and Safety, respectively, ISO 9001, ISO 14001 and OHSAS 18001 is increasing, however, managing these three separate systems is a challenge. Some of the reasons that we presented in these articles for implementing IMS include satisfying customers’ requirements and responding to government appeals. Finally, we identified from the portfolio of articles the most cited authors, articles, barriers and difficulties for implementing IMS.